Visualising the Eastern Front: Heimatschutz and Survey Photography During the First World War - Manikowska, Ewa (Acta Poloniae Historica, 2016)
This article discusses the photographic surveys undertaken on Polish occupied lands in the framework of the German war-time Landeskunde and Kunstschutz research projects. It presents the photographic collections produced in the General Government and Ober Ost, held in larger and smaller archives, widely popularized both on the front and at home by means of the press, albums, scientific and popular publications, postcards, lantern lectures and exhibitions. It argues that the advancement of the front provided a unique opportunity for such explorations and that the German surveys were the first of such reach and scale to cover all of Polish territories. The article also traces the possible close collaboration between German and Polish scholars, photographers and institutions. In particular it juxtaposes the survey initiatives undertaken by the Warsaw civic societies with the projects of the Landeskundliche Kommission and the Warsaw Hofbauabteilung. In addition, it focuses on the close collaboration between Jan Bułhak and the German art historians in Vilnius.